Note on Elzaki Transform of Distributions and Certain Space of Boehmians (Global Journal of Science Frontier Research, 2012)
The Elzaki transform transform was discussed in [19] as a motivation of the classical Sumudu transform. In this article, we extend the Elzaki transform to a space of tempered distributions (distributions of slow growth) by known kernel method. Further, we establish two spaces of Boehmians so that the Elzaki transform is well de.ned. Certain theorems are established in some details.
Keywords: Generalized function; Elzaki Transform; Sumudu Transform; Tempered Distribution; Boehmian Space